Morphometric and meristic study of four freshwater fish species of river Ganga - KAMBOJ, NITIN; KAMBOJ, VISHAL (The Indian Journal of Animal Sciences, 2019)
The present study was carried out in Ganga River from Devprayag to Haridwar district of Uttarakhand to analyse morphometric measurement and meristic count of some selected fish species during April 2017 to March 2018. Specimens (20) of each fish species were collected from different zones of river Ganga and 24 morphometric measurements and eight meristic count parameters were studied for each fish species. The total length and weight of Cyprnius carpio ranged from 14–18 cm and 60–78 g; Mahseer fish species 21–28 cm and 120–185 g; 20–26 cm and 100–160 g (Labeo rohita) and 17–25 cm and 20–34 g (Xenentodon cancila) respectively were recorded during the study period. The regression coefficient ‘b’ shows higher growth rate with respect to Total length. It was maximum in case of standard length (b= 1.115) and lowest in pelvic fin length (b=0.146) for Cyprnius carpio, maximum in case of standard length (b=1.132) and lowest in pectoral fin length (b=0.126) for Mahseer, maximum in case of Fork and standard length (b=0.995) and lowest in length of caudal peduncle (b=0.135) for Labeo rohita and maximum in case of standard length (b=1.020) and lowest in case of pelvic fin length (b=0.018) for Xenentodon cancila respectively.